Immunomodulatory effects of individual and combined mycotoxins in the THP-1 cell line. (October 2016) - Solhaug, A.; Karlsøen, L.M.; Holme, J.A.; Kristoffersen, A.B.; Eriksen, G.S.
Abstract: Mycotoxins commonly contaminate food and may pose a risk for disease in humans and animals. As they frequently co-occur, mixed exposures often take place. Monocyte function, including differentiation into active macrophages, is a central part of the immune response. Here we studied effects of naturally co-occurring mycotoxins in grain on monocyte function, and effects of individual and combined exposure on the differentiation process from monocytes into macrophages. The THP-1 cell line was used as a model system. The mycotoxins 2-amino-14, 16-dimethyloctadecan-3-ol (AOD), alternariol (AOH), enniatin B (ENNB), deoxynivalenol (DON), sterigmatocystin (ST) and zearalenone (ZEA) differently affected cell viability in THP-1 monocytes, with DON as the most potent. AOH, ZEA and DON inhibited differentiation from monocytes into macrophages. Using this differentiation model, combined exposure of AOH, ZEA and DON were mainly found to be additive. However, the combination AOH + ZEA had somewhat synergistic effect at lower concentrations. Furthermore, alterations in macrophage functionality were found, as single exposure of AOH and ZEA inhibited lipopolysaccharide (LPS) induced TNF-α secretion, while DON increased this response. Overall, the mycotoxins affected monocyte viability and differentiation into macrophages differently. Combined exposures affected the differentiation process mainly additively. Graphical abstract: Highlights: Mycotoxins differently affected proliferation and survival of THP-1 monocytes. AOH, DON and ZEA, reduced differentiation from monocytes into macrophages. The combined effects of these mycotoxins were mainly additive. Prediction models: concentration addition, independent action and isobolograms AOH, DON and ZEA affected LPS induced macrophage activation.